ChemInform Abstract: Polymorphism, Phase Transitions, and Thermal Expansion of K3Lu(PO4)2. Issue 14 (8th April 2014) - Farmer, J. Matt; Boatner, Lynn A.; Chakoumakos, Bryan C.; Rawn, Claudia J.; Mandrus, David; Jin, Rongying; Bryan, Jeff C.
Abstract Single crystals of K3Lu(PO4)2 are prepared from mixtures of Lu2O3 and K4P2O7 (Pt crucible, 1508 K, 4 h).